1996
DOI: 10.1016/0014-5793(96)00698-9
|View full text |Cite
|
Sign up to set email alerts
|

F protein induced fusion of Sendai viral envelopes with mouse teratocarcinoma cells through LeX‐LeX interaction

Abstract: Materials and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…This is consistent with serine protease-like activity associated with Sendai virus and its reconstituted envelopes (Fand HN-virosomes) with both F and HN glycoproteins (21). We have recently established that Sendai virus F protein in F-virosomes can induce complete membrane fusion, provided that the latter are bound tightly to the target cell membrane (5,9,23). Our results are consistent with the studies on other paramyxoviruses which show F protein in absence of HN can induce syncytium formation (2,19).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This is consistent with serine protease-like activity associated with Sendai virus and its reconstituted envelopes (Fand HN-virosomes) with both F and HN glycoproteins (21). We have recently established that Sendai virus F protein in F-virosomes can induce complete membrane fusion, provided that the latter are bound tightly to the target cell membrane (5,9,23). Our results are consistent with the studies on other paramyxoviruses which show F protein in absence of HN can induce syncytium formation (2,19).…”
supporting
confidence: 63%
“…We have recently shown that F-virosomes (prepared from Sendai virus grown in the allantoic sac of 10-to 11-day-old embryonated chicken eggs at 37°C) can bind and fuse to hepatoblastoma cells (HepG2 cells) in culture (and liver cells in vivo) through a strong interaction between the terminal galactose moiety of F protein and asialoglycoprotein receptor on the membrane of the HepG2 (liver) cells (5)(6)(7)9). It has also been observed that HN glycoprotein is not essential for F-induced membrane fusion, provided that F can be tightly bound to the target membrane, either through a heterologous membrane ligand like influenza virus hemagglutinin (8) or through carbohydrate-carbohydrate interactions (23), and that Sendai virus and F-virosomes treated with PMSF and APMSF (specific serine protease inhibitors) failed to catalyze membrane fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The Sendai virus envelope contains two glycoproteins; hemagglutinin-neuraminidase (HN), as well as fusion (F) proteins that are anchored in the outer leaflet of the viral lipid bilayers. The F glycoprotein, which consists of two disulfide-linked polypeptides (F1 and F2), is required for viral entry into host cells, as well as for membrane fusion (Kumar et al, 1997;Kumar and Sarkar, 1996). The HN glycoprotein mediates the attachment of the virus to the cell surface via sialic acid termini of glycoproteins or glycolipids, and may also actively participate in the process of virus-cell fusion (Nakanishi et al, 1982;Bagai et al, 1993).…”
Section: Introductionmentioning
confidence: 99%